2008
DOI: 10.2139/ssrn.1099898
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk Transfer in Banking Markets with Hard and Soft Information

Abstract: We present a banking model with imperfect competition in which borrowers' access to credit is improved when banks are able to transfer credit risks. However, the market for credit risk transfer (CRT) works smoothly only if loans are based on hard (verifiable) information. When information is soft, banks have an incentive to grant unprofitable loans in order to transfer them to other parties, leading to an increase in aggregate risk. Nevertheless, the introduction of CRT generally leads to an increase in welfar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Based on Diamond (1984), already Hellwig (1994 a) had suggested that a securitization of the interest rate risk inherent in long-term assets would have to be engineered in such a way that asset-specific return risks would stay with the intermediary since otherwise the intermediary would have too little incentive to take care in selecting and monitoring loan clients. Hakenes and Schnabel (2008) provide a formal model of the moral hazard in origination that is generated by credit risk transfer. Because the counterparties are aware of the moral hazard and prices are set accordingly, in their model, the overall welfare effects of credit risk transfers are positive despite the mora hazard that they generate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Diamond (1984), already Hellwig (1994 a) had suggested that a securitization of the interest rate risk inherent in long-term assets would have to be engineered in such a way that asset-specific return risks would stay with the intermediary since otherwise the intermediary would have too little incentive to take care in selecting and monitoring loan clients. Hakenes and Schnabel (2008) provide a formal model of the moral hazard in origination that is generated by credit risk transfer. Because the counterparties are aware of the moral hazard and prices are set accordingly, in their model, the overall welfare effects of credit risk transfers are positive despite the mora hazard that they generate.…”
mentioning
confidence: 99%
“…45 Demyanyk and Van Hemert (2008) also show that the assessment is unchanged if foreclosure rates, rather than delinquency rates, are considered. Hakenes and Schnabel (2008) attribute such quality deterioration to intensifying competition by originators, Rona-Tas and Hiß (2008) to the effects of increased gaming by mortgage borrowers (and brokers?) on the reliability of credit scores.…”
mentioning
confidence: 99%